The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/jmri.21954
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femur bone marrow blood perfusion indices are reduced in hypertensive rats: A dynamic contrast‐enhanced MRI study

Abstract: Purpose: To investigate the differences in proximal femoral bone marrow blood perfusion indices between hypertensive and normotensive rats using perfusion magnetic resonance imaging (MRI). Materials and Methods:Six-month-old male spontaneously hypertensive rats (SHR) and Wistar Kyoto rats (WKY) were used (12 of each). Dynamic contrastenhanced MRI of the right hip was performed after bolus injection of Gd-DOTA administered through a tail vein cannula. In all, 800 images were acquired at 0.6 sec/ image. Regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…At 6 months, they develop a sustained hypertension compared with their normotensive control strain, the Wistar Kyoto (WKY) rats. [27][28][29][30][31] The hypertensive rats exhibit brain changes similar to ageing rats [27][28][29][30] but can be more advanced than the age-matched normative rats. In this study, we aimed to investigate the changes of T1r values in rat brains associated with normal ageing process in Sprague-Dawley (SD) rats, WKY rats and SHRs.…”
Section: Introductionmentioning
confidence: 99%
“…At 6 months, they develop a sustained hypertension compared with their normotensive control strain, the Wistar Kyoto (WKY) rats. [27][28][29][30][31] The hypertensive rats exhibit brain changes similar to ageing rats [27][28][29][30] but can be more advanced than the age-matched normative rats. In this study, we aimed to investigate the changes of T1r values in rat brains associated with normal ageing process in Sprague-Dawley (SD) rats, WKY rats and SHRs.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,20,21,22 Few studies can be found correlating endodontic disease and hypertension. Allareddy et al, 23 conducted a retrospective study where they found that 24.6% of patients hospitalized for periapical abscesses were hypertensive.…”
mentioning
confidence: 99%
“…As a normotensive control, it was used the wistar-kyoto strain. Because SHR and WKY have the same genetic background except hypertension, the WKY strain has been used in most of studies and accepted as the most appropriate normotensive control for SHR 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…A medicina periodontal vem demonstrando que alterações sistêmicas tais como diabetes, hipertireoidismo, dislipidemia e doenças cardiovasculares podem influenciar a inflamação periodontal. Alguns estudos epidemiológicos e experimentais têm mostrado uma associação entre a severidade da periodontite e a hipertensão 11,12,20,23 e também tem associado a hipertensão com a sobrevivência dental 11,12,24,25 .…”
Section: Introductionunclassified
See 1 more Smart Citation